Associations between TLRs 2 and 4, and β-lactam antibiotics in COPD patients complicated with pulmonary infections - Lou, Yunchen; Jiang, Guofeng (The Journal of Infection in Developing Countries, 2024)
Introduction: Chronic obstructive pulmonary disease (COPD) is the third leading cause of death in the world. We aimed to investigate the associations between toll-like receptors 2 and 4 (TLR-2 and TLR-4) and β-lactam antibiotics in COPD patients complicated with pulmonary infections. Methodology: A total of 156 COPD patients complicated with pulmonary infections were included. Their blood gas, airway resistance, health status, expression levels of TLR-2 and TLR-4, and pulmonary function were analyzed after treatment with β-lactam antibiotics. Results: Blood gas indices oxygen saturation, partial pressure of oxygen, and partial pressure of carbon dioxide at one day before treatment, on the fifteenth day of treatment, and on the first day after the end of treatment showed significant differences (p < 0.01). Significant differences were also detected in airway resistance indices (p < 0.01). The differences in the mRNA expression levels of TLR-2 and TLR-4 were significant (p < 0.05). Downward trends were observed in the clinical pulmonary infection score and acute physiology and chronic health evaluation II score, which indicated alleviation of the disease. Pulmonary function indices recorded vital capacity (VC)/predicted VC (%), recorded forced vital capacity at 1 s (FEV1)/predicted FEV1 (%), and residual volume/total lung capacity were significantly different (p < 0.05). Conclusions: β-Lactam antibiotics had obvious therapeutic effects on COPD patients complicated with pulmonary infections, probably by suppressing or attenuating TLR-2- and TLR-4-mediated inflammatory responses. It is necessary to comprehensively evaluate and choose appropriate antibiotics, aiming for maximum relief of the pain to help patients recover quickly.